Explanation and design of mentoring in order to promote human resources activities in the National Company of Southern Oil-bearing Regions - Ali Ghasemi Ghasemvand; Vahid Chenari; Mehrdad Hamari; Seyyed Ali Akbar Ahmadi (مدیریت و چشم انداز آموزش)
Abstract The aim of the current research is to explain and design mentoring in order to improve human resources activities in the National Company of Southern Oil Regions. The current research is of mixed type (qualitative-quantitative). In the qualitative part, the necessary factors and infrastructures of the model were identified through interviews with 11 experts who were selected using the snowball sampling method; and in the quantitative part, the community consisted of 105 experts and human resource managers of the southern National Petroleum Regions Company, and stratified random sampling method was used. In the qualitative stage, the theme analysis method is used. Experts' opinions were used to check the validity of the qualitative data collection tool, and thematic analysis was uded to check the reliability of the findings. MAXQDA 10 software was used to analyze the qualitative data; and in the quantitative stage, data analysis has been done through questionnaires and structural equations using SPSS, SmartPLS software. Based on the results of the research, 16 themes and in fact the necessary infrastructures for the design of the model were obtained, which are: organizational communication, mentoring evaluation, organizational trust, organizational training, employee development, organizational commitment, employee empowerment, employee socialization, organizational structure, organizational factors, knowledge management, career path management, human resources management, organizational implementation barriers, organizational performance results, and mentor's individual characteristics. Finally, based on the obtained results, the mentoring model was designed in order to improve human resources activities. Extended abstract Introduction Today, organizations have well understood that in order to succeed in the complicated global economy and to survive in the competitive business environment, they need to have the best talents. At the same time as understanding the need to recruit, develop and maintain talents; organizations have realized that talents are critical resources (Abadeh et al, 2023). Today, at least half of the top 1000 leading companies in the world provide mentoring in various forms to their employees. Organizations such as NASA, Vodafone, Coca-Cola, etc. are among the organizations that have included mentoring in their human resources training activities. Even associations and institutions active in the field of training and improvement, such as the American Training and Improvement Association, the Personnel and Improvement Association, the American Management Association, or the International Federation of Coaches, carry out extensive activities in the field of mentoring (Kosariye et al., 2020). Official mentoring programs in organizations are implemented with a special focus on organizational development. Organizational development and culture change; Mentoring can help establish a connection between the organization's values, mission and duty. One-to-one communication helps employees understand the organizational culture and implement any necessary changes. Educational support; the mentoring method helps fill the gap between theory and practice through more transfer of knowledge and learning. Formal education and learning is completed by the practical knowledge and experience of a professional and skilled worker. Retention and maintenance of employees; The mentoring method creates a motivated and encouraging environment through interactions, training and role modeling that facilitates the internal progress of the organization and increases the welfare of employees. Mentors increase success, satisfaction, promotion and job opportunity (Tyler & MMckenzie, 2011). Therefore, the current research is looking for the answer of following question: How is the explanation and design of mentoring in order to promote human resources activities in the National Company of Southern Oil Regions? Theoretical Framework Human resources Human resources are a valuable intangible asset in an organization. Their wants and needs are different and difficult to understand. Due to the increase in the size of the industry and the complexity related to its operations and human factors, a number of organizations have used mentoring programs. Mentoring helps to increase the morale of employees and motivates them to achieve the goals of the organization. Through mentoring, organizations see their employees as better people and gain knowledge about the work needs and personal needs of employees. Just like a discipline that integrates organizational goals and personal goals, organizations gain many benefits through mentoring (Daneshmandi et al, 2018). Mentoring Mentoring is a type of learning process in which individual and mutual helping relationships are achieved through a focus on success (Rajabpor et al, 2015). In this type of learning, emotional support is a key component (Haran & Jeyaraj, 2019). In the mentoring relationship, the mentee learns and grows through conversations with experienced mentors who share their knowledge and experience, and this Learning is integrated with their thinking and action (Rajabpor, 2020). Abdollahi & Heshmati Navabi (2023) investigated coaching as an appropriate strategy for the development of medical faculty members in higher education: a systematic review. The results showed that the mentoring program consists of three stages: "targeting and familiarization with the implementation of the mentoring program", "implementing the mentoring program" and "evaluating the mentoring program." Implementation approaches included a traditional one-on-one coaching program, a peer coaching program, and a distance learning coaching program. By identifying the stages and types of mentoring programs, this study showed that their use, especially the distance education guidance program, has led to the advancement of faculty members in various fields. A mixed approach to program evaluation can provide more appropriate views of the effects of these programs. Gholipur et al, (2022) investigated the presentation of the mentoring model and analyzed the factors affecting its successful implementation in the Hamrah-e Avval company. The results of the interviews were analyzed by theme analysis and using Brown and Clark's approach. Factors affecting the implementation of the mentoring process in 17 sub-categories and 3 main categories; included planning, implementation and evaluation and feedback. Then, in the quantitative phase of the research, the main and subcategories were evaluated using the fuzzy hierarchical analysis technique. The results in the second step of the research showed that the category of implementation is the most important among the three main categories of implementing the mentoring process in the Hamrah-e Avval Company; and after that, the categories of "planning" and "evaluation and feedback" are in the second and third ranks. Research methodology The current research is of mixed type (qualitative-quantitative). In the qualitative part, the necessary factors and infrastructures of the model were identified through interviews with 11 experts who were selected using the snowball sampling method; and in the quantitative part, the community consisted of 105 experts and human resource managers of the Southern National Petroleum Regions Company, and stratified random sampling method was used. Research findings The Max Kyuda software was used to analyze the qualitative data, and in the quantitative stage, the data analysis was done through questionnaires and structural equations using (SPSS, SmartPLS) software. Based on the results of the research, 16 themes and in fact the necessary infrastructures for the design of the model were obtained, which are: organizational communication, mentoring evaluation, organizational trust, organizational training, employee development, organizational commitment, employee empowerment, employee socialization, organizational structure, organizational factors, knowledge management, career path management, human resources management, organizational implementation barriers, organizational performance results, and mentor's individual characteristics. Finally, based on the obtained results, the mentoring model was designed in order to improve human resources activities. Conclusion The current research has been carried out with the aim of explaining and designing mentoring in order to improve human resources activities in the National Company of Southern Oil Regions. The results of this research corresponds with the results of Derex (2021), Bas et al, (2018), Ebrahimpour et al, (2021), Perasad et al, (2019), Mendez et al, (2017), Safdari & ghrone (2022), Deipite & Shalin (2017), Zarabi et al, (2018), Maghboli et al, (2019), Perasad et al, (2019), Safdari & Ghoroneh (2022), Daneshmand et al, (2018), Bass et al, (2018), Pourhossein (2018), Safdari & ghrone (2022), and Deipite & Shalin (2017). From the review of researchers' opinions, it is concluded that the necessary factors and infrastructures for the implementation of mentoring are: The structure of mentoring, determining the supervisor of mentoring implementation, training, creating a mentoring culture, mentoring evaluation, and service compensation. It can be concluded that, according to the background of the research and by studying the opinion of the researchers and by studying the researches, mentoring improves the activities of Human resources include: socialization of training and development, performance management, career path and succession, and preservation and maintenance of human resources. According to the findings of the research, for the optimal use of human resources in planning in the field of mentoring evaluation, it is suggested: - Due to the fact that the human resources activities in the National Company of Southern Oil-bearing Regions need to be improved and the use of management systems and attention to these activities will improve the human resources activities, and if human resource activities are performed well; the performance of human forces and human resources of the organization will improve, and the achievement of the organization's goals depends on the performance of its human resources, and the proper performance of the organization's human resources will make the organization's goals effective and efficient. It is recommended to use mentoring system in order to improve human resource activities.